2015
DOI: 10.1371/journal.pone.0135274
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Same-Day Access and Continuity in Primary Care and Emergency Department Visits

Abstract: We examined how emergency department (ED) visits for potentially preventable, mental health, and other diagnoses were related to same-day access and provider continuity in primary care using administrative data from 71,296 patients in 22 VHA clinics over a three-year period. ED visits were categorized as non-emergent; primary care treatable; preventable; not preventable; or mental health-related. We conducted multi-level regression models adjusted for patient and clinic factors. More same-day access significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Engagement and care coordination through Assertive Community Treatment (ACT) teams has resulted in improved health outcomes and decreased use of acute services in severely mentally ill homeless populations (39). Also, same-day primary care in the VA system has been associated with decreased use of EDs for problems that can be managed as an outpatient and might not necessarily require acute services (40). Perhaps most striking is the growing number of studies that have found decreased use of acute services after entry in to supportive housing with case management (4143).…”
Section: Discussionmentioning
confidence: 99%
“…Engagement and care coordination through Assertive Community Treatment (ACT) teams has resulted in improved health outcomes and decreased use of acute services in severely mentally ill homeless populations (39). Also, same-day primary care in the VA system has been associated with decreased use of EDs for problems that can be managed as an outpatient and might not necessarily require acute services (40). Perhaps most striking is the growing number of studies that have found decreased use of acute services after entry in to supportive housing with case management (4143).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that if primary care is made more accessible and available, patients will visit EDs less frequently, but existing literature provides mixed evidence to support such a rationale . Some evidence suggests that having a regular source of PHC and continuity of care can significantly reduce the likelihood of inappropriate use of the ED and that frequent ED visitors are less likely to report that they get what they need from their PHC . Bolíbar et al found that in a city in Spain, users of health centres that had been the target of organizational reform attended less the ED than those who had not been the target of intervention, but ED use was inappropriate regardless of the PHC model.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have explored the relations between access and continuity of care, 16,25,38,39,45,[50][51][52][53][54][55][56][57][58][59][60] access and emergency department use, 16,[61][62][63][64][65][66][67][68][69][70][71][72] and continuity of care and emergency department use. 4,[12][13][14][15]63,73,74 Various algorithms have been used to develop virtual panels to associate patient to activity to specific physicians.…”
Section: Discussionmentioning
confidence: 99%